Residual stress simulation for bimetallic sleeve roll constructed by shrink-fitting in comparison with bimetallic solid roll - Aridi M.R.; Rafar R.A.; Noda N.-A.; Sun Z.; Sano Y.; Takata K.; Takase Y. (Elsevier Ltd, 2024)
Next-generation rolls such as super-cermet rolls can be manufactured only by adopting a sleeve roll structure where the shaft is shrink-fitted into the sleeve. To prevent sleeve cracking due to sleeve slip, reducing the residual stress at the inner surface of the sleeve is important. In this paper, therefore, two extreme manufacturing processes are investigated to provide suitable residual stress to the sleeve